Influence of sugars on biofilm formation of Staphylococcus epidermidis - Vashchenko, A. O.; Voronkova, Y. S.; Kulyk, E. E.; Snisar, O. S.; Sidashenko, O. I.; Voronkova, O. S. (Regulatory Mechanisms in Biosystems, 2021)
The problem of biofilm formation by clinical strains of opportunistic bacteria is one of the most significant for medicine, because in a state of biofilm bacteria become more resistant to environmental factors, including antibiotics, a situation that can cause failure of treatment. Among opportunistic pathogens staphylococci are of special interest. Knowledge about the peculiarities of biofilm formation of these strains, in particular the polysaccharide biosynthesis, can be used for creation of a strategy of prophylaxis of different lesions that bind with staphylococci. The effect of different concentrations of the most widespread sugars (glucose, sucrose, lactose, galactose) on the activity of biofilm formation by strains of Staphylococcus epidermidis was investigated. Strains of S. epidermidis (n = 7) were isolated from the reproductive tract of women with dysbiosis. The cultures were grown in universal synthetic media with concentration of one of the listed sugars (0.5–3.0%) during 72 h. Results were obtained colorimetrically. We studied the number of cells in biofilm and the index of biofilm formation. The largest number of cells in the biofilm was observed when the culture incubated in a medium with 2.0% of glucose (increase of 25.3 times compared to control). The amount of CFU in the control biofilm was 9.96 lg CFU/mL. The glucose concentration of 3.0% inhibited the biofilm formation: the number of cells in the biofilm was 569 times less compared to the control. The highest value of biofilm formation index was 7.2, which was 1.3 times higher than the control (5.4). In the presence of lactose and galactose in nutrient medium in concentrations from 1.0% a decrease in the number of cells and biofilm formation index were observed. The received data show that process of biofilm formation is significantly dependent on external sources of sugars, which can indicate the possibility of their use as antibiofilm drug compounds, which inhibit membrane transport of sugars in bacteria.